Pengaruh Kinerja Corporate Social Responsibility (Csr) Terhadap Persistensi Laba Pada Perusahaan-Perusahaan Berkapitalisasi Besar - Lestari, Intan Puji (Business Accounting Review, 2016)
The affect of corporate social responsibility (CSR) towards firm financial performance by using financial ratio such as ROA, ROE and ROS had been studied before. However, there were only a few studies about the effect of CSR on earning persistence. The aim of this research was to examine the affect of corporate social responsibility (CSR) toward earning persistence in big capitalization firms in Indonesia.            This study was conducted on big capitalization companies in Indonesia in the period 2010 to 2014 with a total sample of 84 firm years. CSR was measured based on57 its completeness compared to GRI 3.1 guideliness. Whereas earning persistence was measured by earnings per share (EPS). The result indicated that CSR had no significant influence toward earning persistence